Street Smarts ↔ Book Smarts: Three Neighborhoods and One University School of Nursing Partnering for Health. (5th July 2016) - Valaitis, Ruta K.; Wahoush, Olive; Murray, Nancy; Isaacs, Sandy; Derbyshire, David; Semogas, Dyanne; Rolfe, Steven
This article describes the development, implementation, and evaluation of an interdisciplinary undergraduate course embedded within a campus–community partnership initiative involving McMaster University School of Nursing, and three urban priority neighborhoods in Hamilton, Ontario, Canada. Students worked together with community residents and faculty to address selected priority community issues identified by neighborhood members. Using the qualitative interpretive description method, the evaluation explored different partners' (students, community residents, and faculty) perceptions of the course (SWOT analysis: strengths, weaknesses, opportunities, and threats, as well as outcomes) as a community engagement and knowledge exchange intervention. Results provide lessons learned and recommendations for future campus–community engaged courses that can be transferred to similar contexts.